The Influence of Service Factors and Operational Effectiveness on Company Management Performance - Saman, Iin Nuraini; Suriyanti, Suriyanti; Akbar, Ahmad Nurwahyudi; Rahmadani, Putri Sri (Economos : Jurnal Ekonomi dan Bisnis, 2024)
In the era of increasingly intense business competition, companies are required to possess strategic capabilities in managing their management performance. One of the main challenges faced by PT. Wira Eka Persadatama Makassar Branch is ensuring that customer service and operational effectiveness function optimally to support the achievement of the company's goals. This study aims to examine the impact of service factors and operational effectiveness on the company’s management performance. The data for this study were obtained from employees at PT. Wira Eka Persadatama Makassar Branch who agreed to participate as respondents. The research utilized primary data collected through questionnaires from 45 respondents, which were then analyzed using multiple linear regression with a quantitative approach. The results of the study indicate that service factors and operational effectiveness have a positive and significant influence on the company’s management performance. These findings highlight the importance of improving service quality and optimizing operations to enhance the company’s performance towards better outcomes.